Identifying students’ needs towards the provision of social support in online learning - Junaidi, Juhazren (Secholian Publication, 2021)
Social support has been found to play an important role in retaining learning and contribute to better understanding and performance among students. This study aims to determine the needs and requirements of learners or students towards the provision of social support in online learning. Random sampling technique was used to select 10 students enrolled in an ICT-based course at one of Malaysian university as respondents. The instrument for this study was a semi-structured interview questions adapted from the works of Sarason et al. (1987). Thematic analysis was performed on the transcribed interview to allow visual interpretation and understanding of the context from each response. This study found that the students had often received and prefer to get social support while learning online. The reasons for their preference were for motivation, understanding, information searching and affirmation. The students were also identified to have preference for social support from the instructor more than from peers and the learning content. Overall, Informational Support is the most expected type of social support by the students. This study provides findings that would assist in the provision of social support through the design and development of an online learning environment.